2018
DOI: 10.1016/j.jcis.2017.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Targeted photodynamic therapy of breast cancer cells using lactose-phthalocyanine functionalized gold nanoparticles

Abstract: Gold nanoparticles (AuNPs), which have been widely used for the delivery of photosensitizers for photodynamic therapy (PDT) of cancer, can be dispersed in aqueous solutions improving the delivery of the hydrophobic photosensitizer into the body. Furthermore, the large surface of AuNPs can be functionalized with a variety of ligands, including proteins, nucleic acids and carbohydrates, that allow selective targeting to cancer tissue. In this study, gold nanoparticles were functionalized with a mixed monolayer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 56 publications
1
58
0
Order By: Relevance
“…PDT can help decrease solid stress and, thereby, modulate microenvironmental factors that influence tumor growth and treatment response, such as hypoxia and interstitial fluid pressure [139][140][141][142][143][144]. To improve selective delivery, the PS can be attached to a variety of targeting moieties, such as carbohydrates, peptides, folic acid and antibodies, or nanocarriers that target markers that are overexpressed on cancer cells [48,97,136,[145][146][147][148][149]. PIT involves the use of an antibody-based PIC to enhance PS selectivity and has been shown to be effective in a variety of cancer types, including ovarian cancer [49,60,61,[67][68][69][70][94][95][96][97].…”
Section: Discussionmentioning
confidence: 99%
“…PDT can help decrease solid stress and, thereby, modulate microenvironmental factors that influence tumor growth and treatment response, such as hypoxia and interstitial fluid pressure [139][140][141][142][143][144]. To improve selective delivery, the PS can be attached to a variety of targeting moieties, such as carbohydrates, peptides, folic acid and antibodies, or nanocarriers that target markers that are overexpressed on cancer cells [48,97,136,[145][146][147][148][149]. PIT involves the use of an antibody-based PIC to enhance PS selectivity and has been shown to be effective in a variety of cancer types, including ovarian cancer [49,60,61,[67][68][69][70][94][95][96][97].…”
Section: Discussionmentioning
confidence: 99%
“…However, in vivo studies showed that M-chlorin PDT led to significantly more tumor suppression than G-chlorin PDT, which was attributed to the affinity of M-chlorin for CD-206 expressing TAMs in addition to cancer cells. These results suggest exciting opportunities for future studies that target multiple (327)(328)(329)(330) cell types with a single targeting moiety to achieve enhanced antitumor effect. Such constructs could potentially achieve synergistic cytotoxicity by killing cancer cells as well as the nonmalignant cells that contribute to tumor maintenance, thereby providing an inherent mechanism for managing the cancer cells that survive initial treatment.…”
Section: Targeted Deliverymentioning
confidence: 96%
“…a). Targeting moieties used for this purpose include folic acid, peptides, antibodies and carbohydrates (Table ), and can be either conjugated to a nanoparticle or directly to a PS.…”
Section: Targeting the Tumor Microenvironment With Photochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…One ZnPc is connected via three carbon atoms (C3Pc), whereas the other is connected via eleven (C11Pc) (Fig 1). 23 In solution, the C11Pc photosensitiser exhibited significantly greater fluorescence than the C3Pc. Intriguingly, despite the shorter anchor chain and the expectant quenching of the fluorescence of the C3Pc photosensitiser, the C3Pc was found to be more fluorescent when attached to the surface of the AuNPs than the C11Pc with the longer chain.…”
Section: Introductionmentioning
confidence: 95%